2023
DOI: 10.1515/tjj-2022-0060
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the choke margin of a mixed flow compressor stage for a micro gas turbine engine

Abstract: In an attempt to reduce engine frontal area, while maintaining a high single stage pressure ratio, mixed flow compressor stages are frequently used in micro gas turbine (MGT) engines. The expansion of the choke margin of such a mixed flow compressor is presented. The use of a crossover diffuser configuration in a mixed flow compressor stage has displayed superior performance results compared to legacy diffuser configurations, especially when geometric restrictions are enforced. A disadvantage of a crossover di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…To expand the operating range of the upgraded CAT250TJ_BL compressor, selected operating range expansion methods discussed in Van Eck [15] are employed. These are discussed below.…”
Section: Baseline Test Compressor Designmentioning
confidence: 99%
See 4 more Smart Citations
“…To expand the operating range of the upgraded CAT250TJ_BL compressor, selected operating range expansion methods discussed in Van Eck [15] are employed. These are discussed below.…”
Section: Baseline Test Compressor Designmentioning
confidence: 99%
“…3) allows the boundary layer to be re-energised, better controlling the boundary layer at various operating points and therefore the overall operating range. Van Eck [15] numerically investigated various tandem vane crossover diffuser configurations and their effect on compressor design point performance and operating range. It was shown that a low solidity front vane configuration displayed a marked increase in choke margin.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations